2021
DOI: 10.2172/1808490
|View full text |Cite
|
Sign up to set email alerts
|

USAID Grid-Scale Energy Storage Technologies Primer

Abstract: This refers to newer PSH installations and older PSH systems may have efficiencies closer to the 60-75% range. **: As CAES relies on both electricity to compress air and a fuel (typically natural gas) to expand the air, its efficiency cannot be readily compared to other storage technologies. The value used in this report represents the ratio of the output of electrical energy to the combined input of electrical energy for the compressor and the natural gas input for expansion, using the heating value of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…In March of 2022, PSH accounted for 23 GW of active storage, while all battery storage, the vast majority of which is lithium-ion (Kamiya, Hassid, and Gonzalez, 2021), accounted for 4 GW of storage (EIA, 2022a). Lithium-ion is an appropriate comparison for PSH because both are time-tested and widely deployed forms of energy storage (Bowen et al, 2021).…”
Section: Lithium-ion Vs Pumped Storage Hydropowermentioning
confidence: 99%
See 3 more Smart Citations
“…In March of 2022, PSH accounted for 23 GW of active storage, while all battery storage, the vast majority of which is lithium-ion (Kamiya, Hassid, and Gonzalez, 2021), accounted for 4 GW of storage (EIA, 2022a). Lithium-ion is an appropriate comparison for PSH because both are time-tested and widely deployed forms of energy storage (Bowen et al, 2021).…”
Section: Lithium-ion Vs Pumped Storage Hydropowermentioning
confidence: 99%
“…LIBs have a highly competitive price. An analysis by the National Renewable Energy Laboratory (NREL) has found that they have one of the lowest costs of grid-scale energy storage with a range of $1408 to $1947 per kilowatt (Bowen et al, 2021). Analysts predict battery costs will fall further over the coming years, even with the disruption by the coronavirus pandemic (Frith, 2021).…”
Section: Costs and Impacts Of Lithium-ion Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Daytime energy generation, by harvesting sunlight, has made tremendous progress over the last two decades (Green et al, 2022). Meanwhile, the standard way to provide renewable energy at night is through energy storage (Bowen et al, 2021). However, in many applications, the possibilities for renewable energy generation without the need for storage are attractive in terms of reducing system complexity or cost.…”
Section: Introductionmentioning
confidence: 99%